THE INDONESIAN ADVOCATES ASSOCIATION AS A CONSTITUTIONAL STATE ORGAN - Sihombing, Daniel Romi (UNISSULA, 2024)
This research aims to analyze PERADI's position in the Indonesian constitutional law system and discover PERADI's authority as a constitutional state organ. This research is qualitative research with a normative juridical approach and data analysis techniques using descriptive analysis. This research concluded that PERADI is a state organ, and PERADI is classified as an Auxiliary agent, which has a special position and authority in its function as a state org General Election Commissionan. Institutions or organs established by the state to implement statutory norms as regulated in the provisions of Article 7 of Law No. 12 of 2011 as amended by Law No. 15 of 2019 concerning Amendments to Laws Number 12 of 2011 concerning the Formation of Legislation is a state institution or state organ. In a modern legal state, the government promotes and organizes general welfare, which Lemaire calls bestuurszorg. This has implications for government work becoming more extensive. The Indonesian Advocates Association, better known by the abbreviation PERADI as an advocate organization that was born from Law No. 18 of 2003, is part of the government's role in improving the welfare of society in the field of law enforcement so that it can be said that Peradi is a state organ that carries out state functions.